Comparison of the Concept of Khiyar According to the School of Fiqh - Hengki Pranata; Rohib Arsadi; Meianna Putri Sitanggang; Rahmadhani Harahap; Nur Sania Dasopang (Al Urwah : Sharia Economics Journal, 2025)
Khiyār is a fundamental mechanism in fiqh muamalah that protects buyers and sellers from losses caused by defects or unclear transactions, a function that has become increasingly relevant in the era of e-commerce where return disputes are frequent. This study aims to analyze and compare the concept of khiyār according to the Hanafi, Maliki, Shafi'i, and Hanbali schools of Islamic jurisprudence. The research employs qualitative library research with a descriptive-comparative approach to classical and contemporary fiqh literature. The results show that although all schools share the same objective of ensuring justice in transactions, they differ in terms of conditions and scope: the Hanafi school restricts khiyār majlis to maintain contractual certainty, the Maliki school applies a flexible approach based on ‘urf, the Shafi'i school adopts a textual interpretation, and the Hanbali school allows broader application. The study concludes that these doctrinal differences constitute a valuable juridical richness that supports the development of adaptive fiqh muamalah and can serve as a comparative foundation for formulating sharia economic regulations and consumer protection policies in modern transactions.